Chronic Pulmonary Silicone Embolism Syndrome Following Saline Breast Implants - Jorden E. Smith; Dianna E. Amariei; Jose Herazo-Maya; Sara Niyazi; Robert F. Ruffolo; Kapilkumar N. Patel; Muhammad R. Quereshi; Jerrold Abraham; Debabrata Bandyopadhyay (Annals of Internal Medicine: Clinical Cases)
Chronic pulmonary silicone embolism syndrome (CPSE) presents as progressive dyspnea occurring after silicone prosthesis implantation. Diagnostic criteria for CPSE include imaging findings of intraparenchymal ground-glass opacities and histologic evidence of silicone microdroplets. CPSE is a very rare entity but has been reported previously secondary to ruptured silicone filled breast implants. Due to safety concerns, many plastic surgeons and patients consider saline-filled breast implants to be a sound alternative. Here, we report a middle-aged woman with biopsy-proven CPSE secondary to saline breast implants, nearly a decade after prosthesis removal.